Genome Sequences of Two Strains of Prototheca wickerhamii Provide Insight Into the Protothecosis Evolution - Guo, Jian; Jian, Jianbo; Wang, Lili; Xiong, Lijuan; Lin, Huiping; Zhou, Ziyi; Sonnenschein, Eva C.; Wu, Wenjuan (Frontiers in Cellular and Infection Microbiology, 2022)
The Prototheca alga is the only chlorophyte known to be involved in a series of clinically relevant opportunistic infections in humans and animals, namely, protothecosis. Most pathogenic cases in humans are caused by Prototheca wickerhamii. In order to investigate the evolution of Prototheca and the genetic basis for its pathogenicity, the genomes of two P. wickerhamii strains S1 and S931 were sequenced using Nanopore long-read and Illumina short-read technologies. The mitochondrial, plastid, and nuclear genomes were assembled and annotated including a transcriptomic data set. The assembled nuclear genome size was 17.57 Mb with 19 contigs and 17.45 Mb with 26 contigs for strains S1 and S931, respectively. The number of predicted protein-coding genes was approximately 5,700, and more than 96% of the genes could be annotated with a gene function. A total of 2,798 gene families were shared between the five currently available Prototheca genomes. According to the phylogenetic analysis, the genus of Prototheca was classified in the same clade with A. protothecoides and diverged from Chlorella 500 million years ago (Mya). A total of 134 expanded genes were enriched in several pathways, mostly in metabolic pathways, followed by biosynthesis of secondary metabolites and RNA transport. Comparative analysis demonstrated more than 96% consistency between the two herein sequenced strains. At present, due to the lack of sufficient understanding of the Prototheca biology and pathogenicity, the diagnosis rate of protothecosis is much lower than the actual infection rate. This study provides an in-depth insight into the genome sequences of two strains of P. wickerhamii isolated from the clinic to contribute to the basic understanding of this alga and explore future prevention and treatment strategies.